L LAW ENFORCEMENT AGAINST ENVIRONMENTAL DAMAGE DUE TO ILLEGAL GOLD MINING (Study in Mandailing Natal Regency) - Ahmad Fauzan Noor; Padian Adi Salamat Siregar (Inspiring Law Journal, 2026)
The environment is crucial for human survival and therefore must be protected and managed sustainably. However, in practice, illegal gold mining activities often cause serious environmental damage. Mandailing Natal Regency is one of the regions with significant gold potential, but many mining activities are carried out without permits and without due regard for environmental aspects. These activities cause various impacts, such as river pollution, forest destruction, and landscape changes. Based on these conditions, this study formulates the problem of environmental damage caused by illegal gold mining, criminal law enforcement against perpetrators, and obstacles faced in the law enforcement process.This study employs an empirical legal research approach with a descriptive analytical approach. Data were obtained through fieldwork and literature review. Data collection was conducted through interviews with relevant parties and a review of primary, secondary, and tertiary legal materials, which were then analyzed qualitatively using a deductive approach. The research results show that illegal gold mining activities in Mandailing Natal Regency have caused various forms of environmental damage, both physical and chemical. This damage includes changes in the landscape due to land clearing, the formation of former mining pits, erosion and landslides around rivers, and water pollution due to the use of hazardous chemicals such as mercury. Furthermore, mining activities also damage forest areas and disrupt the balance of the ecosystem. Criminal law enforcement against perpetrators of illegal gold mining has essentially been carried out by law enforcement officials through preventive and repressive efforts. However, in practice, law enforcement still faces various obstacles, such as limited apparatus resources, weak oversight, and socio-economic factors of communities that depend on mining activities for their livelihoods.